ANALISIS DAMPAK PENGGUNAAN PEMBELAJARAN DARING DI SMK DALAM MENINGKATKAN PEMAHAMAN DAN KETERAMPILAN SISWA PADA MATA PELAJARAN GAMBAR TEKNIK BANGUNAN - Ganang Trinidad (ADISAM PUBLISHER, 2024)
This research aims to analyze the effect of using online learning in learning building engineering drawings on students' conceptual understanding and development of practical skills. The research will evaluate the effectiveness of online learning in facilitating an in-depth understanding of the principles of building engineering drawing as well as students' ability to apply them practically. Apart from that, this research will also examine factors that influence the success of online learning, such as the level of interactivity, accessibility and quality of learning content